The effectiveness of early mobilization intervention on mobilization ability in post caesarean section patients - Rengganis Marcella Aulia Rachman; Chairul Huda Al Husna (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: The rate of cesarean sections continues to rise globally, reaching around 21%, and in Indonesia, it reaches 17–18% of all deliveries. Post-cesarean section patients often experience limited mobility due to pain and muscle weakness, necessitating effective interventions such as early mobilization to prevent complications and accelerate recovery. Purpose:  To determine the effectiveness of early mobilization in improving mobilization ability in post-cesarean section patients. Method: The study design used a case study approach in two post-cesarean section patients who met the inclusion criteria. Early mobilization intervention was provided according to standard operating procedures (SOP), including ROM exercises, position changes, sitting exercises at 6 hours postoperatively, and standing and walking exercises at 8 hours postoperatively. Evaluation was conducted over three treatment sessions to assess changes in mobilization ability. Results: Prior to the intervention, both patients experienced mobility limitations in the form of decreased muscle strength, limited range of motion, pain, and anxiety when moving, with mobility scores in the moderate category (scale 3). After three sessions of early mobilization intervention, there was a significant improvement in all mobility indicators, including muscle strength, ROM, and standing and walking ability. Mobility scores increased to the high category (scale 5). Early mobilization has been proven effective in accelerating recovery and increasing independence in post-cesarean section patients. Conclusion: This study demonstrates that early mobilization intervention is effective in improving mobility in post-cesarean section patients. Prior to the intervention, patients experienced mobility limitations in the form of decreased muscle strength, limited range of motion, pain, and anxiety about moving.